Improving schools with blended learning how to make technology work in the modern classroom - Yeigh, Tony; Fradale, Paul; Lawless, Edward; Lynch, David; Turner, David; Willis, Royce (Abingdon, Oxon Routledge, Taylor & Francis Group, 2021)
Improving Schools with Blended Learning is specifically designed to address the important issues needed to successfully modernise education within the context of technological change. It does this by first providing a clear roadmap for designing Blended Learning environments able to respond to the technological imperatives challenging schools at present, and then illustrating this roadmap via specific, original research that details the 'how to' aspects of a successful technology-based design process. School leaders, teachers, teacher education students and researchers will all find highly relevant information about how to manage for disruption in the new and informative approach to Blended Learning (BL) they will discover in this book. This book arose from two different research projects the authors have been pursuing over the last 3-5 years, including school improvement research and Blended Learningresearch designed to investigate the role of technology in effective teaching and learning. By combining the insights gained from these two different research areas, this book is able to present a novel understanding of BL that is both insightful and clearly evidence-based. Improving Schools with Blended Learning also provides several original contributions to specific knowledge in the areas of BL and school improvement that most educators will find highly useful, including the use of BL schemas, a clear and extended BL continuum, how to measure and evaluate the success of BL, how to scaffold teacher ICT knowledge and skills, and a specific process for contextualising applied BL in relation to the disruption' imperatives of the Knowledge Economy.
Chapter 1: Education and schooling in the digital age. Chapter 2: The case for education reform. Chapter 3: Educational disruption: Why all the fuss about Blended Learning? Chapter 4: What does the research evidence say about effective schools? Chapter 5: Exploring the key role played by school leaders in relation to educational change Chapter 6: What does the research evidence say about Blended Learning? Chapter 7: A Vision for the future of schooling: Positioning Blended Learning in relation to School Improvement. Chapter 8: Using embedded Blended Learning to create the outstanding school. Chapter 9: Taking stock of Blended Learning as a school-based reform journey.
Includes bibliographical references and index.
Keywords: Blended learning; Educational technology